The first selective VAP-1 inhibitor in China, TT-01025-CL: safety, tolerability, pharmacokinetics, and pharmacodynamics of single- and multiple-ascending doses - Yang, Yuanxun; Yu, Lei; Sheng, Zejuan; Lin, Hui; Weng, Zuyi; Song, Wei; Cao, Bei; Zhao, Yu; Gao, Yingsheng; Ni, Shumao; Wang, Huimin; Ma, Tingting; et al. (Frontiers in Pharmacology, 2024)
Introduction: TT-01025-CL is an oral, irreversible small molecule that potently inhibits vascular adhesion protein-1 (VAP-1) for the treatment of inflammation associated with non-alcoholic steatohepatitis (NASH). The objectives of this study were to evaluate the safety/tolerability, pharmacokinetics, and pharmacodynamics of TT-01025-CL, a VAP-1 inhibitor, in healthy Chinese volunteers. Methods: Double-blind, placebo-controlled, dose-escalation studies were conducted in subjects randomized to receive oral once-daily TT-01025-CL (ranges: 10–300 mg [single dose]; 20–100 mg for 7 days [multiple doses]) or placebo under fasting conditions. Safety and tolerability were monitored throughout the study. Pharmacokinetic (PK) parameters were determined using non-compartment analysis. The activity of semicarbazide-sensitive amine oxidase (SSAO)-specific amine oxidase and the accumulation of methylamine in plasma were evaluated as pharmacodynamic (PD) biomarkers. Results: A total of 36 (single-dose group) and 24 (multiple-dose group) subjects were enrolled in the study. No serious adverse events (AEs) were reported, and no subject discontinued due to an AE. All treatment-emergent adverse events (TEAEs) were mild and moderate in intensity. No dose-dependent increase in the intensity or frequency of events was observed. TT-01025-CL was rapidly absorbed after administration. In the single-ascending dose (SAD) study, median Tmax ranged from 0.5 to 2 h and mean t1/2z ranged from 2.09 to 4.39 h. PK was linear in the range of 100–300 mg. The mean Emax of methylamine ranged from 19.167 to 124.970 ng/mL, with mean TEmax ranging from 13.5 to 28.0 h. The complete inhibition (>90%) of SSAO activity was observed at 0.25–0.5 h post-dose and was maintained 48–168 h post-dose. In the multiple-ascending dose (MAD) study, a steady state was reached by day 5 in the 40 mg and 100 mg dose groups. Negligible accumulation was observed after repeated dosing. PK was linear in the range of 20–100 mg. Plasma methylamine appeared to plateau at doses of 20 mg and above, with mean Emax ranging from 124.142 to 156.070 ng/mL and mean TEmax ranging from 14.2 to 22.0 h on day 7. SSAO activity in plasma was persistently inhibited throughout the treatment period. No evident change in methylamine and SSAO activity was observed in the placebo groups. Conclusion: TT-01025-CL was safe and well-tolerated at a single dose of up to 300 mg and multiple doses of up to 100 mg once daily for 7 consecutive days. Absorption and elimination occurred rapidly in healthy volunteers. Linearity in plasma exposure was observed. TT-01025-CL inhibited SSAO activity rapidly and persistently in humans. The profile of TT-01025-CL demonstrates its suitability for further clinical development.